Mammalian Cells with Altered Forms of RNA Polymerase II - Chan, V. L. (1972)
Mutants of Chinese hamster ovary cells that are resistant to α-amanitin can be isolated. At least some of these mutants contain an altered form of DNA-dependent RNA polymerase II, as indicated by its resistance to α-amanitin. These results indicate that mutation to α-amanitin resistance involves a change of a structural gene.